Handbook of school improvement how high-performing principals create high-performing schools - Blase, Jo Roberts; Blase, Joseph; Phillips, Dana Yon.; Sage eBooks (Thousand Oaks, Calif. : Corwin, 2010)
A guide to administrative and instructional leadership, this book poses two key questions for discussion: 'What is a high-performing school?' and 'What does a head teacher do to create a high-performing school?'.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: School improvement programs -- United States -- Handbooks, manuals, etc; School principals -- United States -- Handbooks, manuals, etc; School management and organization -- United States -- Handbooks, manuals, etc; School supervision -- United States -- Handbooks, manuals, etc; Electronic books